Legal Protection in Unauthorized Commercial Restaurant Lease Transfers - I Gusti Ngurah Darma Putra; Ni Luh Made Mahendrawati; Ni Komang Arini Styawati (Inovasi Pratama Internasional. Ltd, 2026)
Unauthorized transfers of commercial restaurant lease rights frequentlycreate legal disputes concerning legal certainty, contractual obligations, and the protection of property owners’ rights. This study examines thelegal protection available in unauthorized commercial restaurant leasetransfers and analyzes the legal consequences arising from leasetransfers conducted without the owner’s consent under Indonesian contract law. The research employs an empirical legal method usingstatutory, conceptual, case study, and socio-legal approaches. Legal materials and empirical findings were analyzed descriptively andqualitatively based on the Indonesian Civil Code, particularly Articles1338, 1548, and 1559. The findings reveal that unauthorized leasetransfers constitute a breach of contract and create legal uncertainty dueto the absence of direct contractual relationships between propertyowners and third parties. Such practices may result in financial losses, loss of control over commercial assets, and prolonged legal disputesaffecting business stability and investment security. The novelty of thisstudy lies in its focus on commercial restaurant lease transfers within thehospitality sector, emphasizing the intersection between contractuallegality, property protection, and commercial business continuity. The study concludes that stronger legal protection is necessary throughexplicit contractual clauses, mandatory written consent, and clearerregulatory frameworks to ensure balanced rights and obligationsbetween parties. Future research is recommended to explorecomparative regulations on commercial lease transfers and alternativedispute resolution mechanisms in international business practices.